Rancangan pencampuran nutrisi otomatis intermitten pada budidaya melon sistem Dutch Bucket untuk urban farming - I Dewa Made Subrata (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2025)
This research aims to design an automatic nutrient mixing system for urban farming Dutch Bucket melon cultivation. The process of mixing nutrients for dutch bucket fertigation system begins by measuring the water level in the tank, then the raw water is flowed into the reservoir until it reaches the maximum height according to the set point. Next, the peristaltic pump is turned on for 300 ms and turned off for 2 s to supply A and B nutrient concentrations alternately until the TDS sensor reaches the set point value. The mixed nutrient solution is circulated continuously into the Dutch bucket and the nutrient runoff from theDutch bucket is flowed back into the reservoir. The research results show that the TDS sensor calibration has a root mean square error (RMSE) value of 28 ppm, the average sensor reliability error is 31,5 ppm and the maximum error is 87,4 ppm from three repetitions under the same conditions. The time required for mixing Aand B nutrient concentrations is 3 minutes. The average nutrient flow rate through the emitter pipe is 7,3 ml/s. The TDS sensor reading values are displayed on the LCD screen and also sent to the ThingSpeak cloud for monitoring purposes. Theoverall test results provide the conclusion that the designed dutch bucket nutrient mixing and fertigation system is able to work well in melon cultivation for urban farming.